IFFARRHEART: uma proposta de solução computacional IoHT para auxiliar a prática pedagógica de educação física - Gonçalves, Denis Pohlmann (2022)
This work aims to present and propose the use of a computational solution that uses the Internet of Things paradigm in health care, or Internet of Health Things (IoHT), aimed at school Physical Education activities. This study sought to integrate various topics of Information Technology, such as Internet of Things, Cloud Computing, Fog Computing, Programming and Computer Networks, in addition to Digital Electronics and 3D Printing, with the purpose of creating computational objects to support the practice. pedagogical teaching at the Instituto Federal Farroupilha Campus São Vicente do Sul (IFFar-SVS). The research problem identified is the manual method of measuring the heart rate (HR) of students, using palpation technique or conventional frequency meters. For the Methodology, first, a systematic review of the literature was carried out, consolidated by Kitchenham (2004), in order to gather all the theoretical support necessary to design this study, and then, an IoHT architecture focused on educational nature was proposed. With the development of this work, objects were built, such as three heart belts and a gateway, and a web page was also implemented with the ThingsBoard platform, thus composing the solution named IFFarHeart. This solution was evaluated in the field involving 33 students and three Physical Education teachers from IFFar-SVS, both in classes and in the training of the institution's athletes. A satisfaction survey was also carried out with those involved, in order to evaluate the use and application of the solution in a teaching environment. As a result, IFFarHeart has enabled teachers to monitor the HR of up to three students simultaneously and in real time, achieving distances of up to 85 m outdoors between the heart rate belts and the gateway, differentiating in these respects from most commercial solutions today. The solution was built to be used completely wirelessly, bringing a great experience to users in terms of mobility, having enough battery for uninterrupted teaching work for a whole day. Based on the answers to the satisfaction survey, the products built had an excellent evaluation in general, being considered attractive and comfortable to use, indicating teaching potential, questions that stimulate students and favor the teachinglearning process, making it possible to engage use by them. On the issue of reliability in the measurement of HR by IFFarHeart, a comparative test was carried out with a similar commercial solution, brand Magene model H64, showing a general average percentage variation of 1.3% with the IFFarHeart solution, considering the commercial solution as a reference.